Challenges and opportunities in upscaling inkjet-printing of OPV - Steinberger, Marc; Qingguang, Xie; Ronsin, Olivier J.J.; Maisch, Philipp; Tam, Kai Cheong; Distler, Andreas; Harting, Jens; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2024)
The power conversion efficiency and long-term stability of organic solar cells have increased tremendously over the past years, reaching up to 19.2% on research cells and 14.5% on large modules. To take the final step towards industrialization, fabrication methods that can be upscaled and directly implemented in industrial processes need to be developed. In recent years, well-known industrial techniques, like drop-on-demand inkjet printing, have been further developed within the organic photovoltaics (OPV) community, as it enables versatile printing of arbitrary, free-form organic solar modules with different colors-a key feature for modern building-integrated photovoltaics and several niche applications of OPV printed on any kind object. In this review, aside a brief summary of recent developments, we provide an overview of the biggest challenges in OPV inkjet-printing and define design rules to overcome these issues. Further perspectives of OPV inkjet-printing conclude the review.
CRIS-Team Scopus Importer:2025-02-04
Keywords: inkjet-printing; organic photovoltaics; upscaling

Classification of Additives for Organic Photovoltaic Devices - Machui, Florian; Maisch, Philipp; Burgues-Ceballos, Ignasi; Langner, Stefan; Krantz, Johannes; Ameri, Tayebeh; Brabec, Christoph (ChemPhysChem, 2015)
The use of additives to improve the performance of organic photovoltaic cells has been intensely researched in recent years. However, so far, no system has been reported for the classification of additives and their functions. In this report, a system for classifying additives according to the fundamental mechanism by which they influence microstructure formation for P3HT:PCBM is suggested. The major parameters used for their classification are solubility and drying kinetics. Both are discussed in detail and their consequences on processing are analyzed. Furthermore, a general mechanism to classify the impact of additives on structure formation is suggested and discussed for different materials relevant to organic photovoltaic devices.
Keywords: additives; fullerenes; ink formulation; organic photovoltaics; polymers

Discriminating bulk versus interface shunts in organic solar cells by advanced imaging techniques - Karl, André; Osvet, Andres; Vetter, Andreas; Maisch, Philipp; Li, Ning; Egelhaaf, Hans Joachim; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2019)
An important aspect when upscaling organic photovoltaics from laboratory to industrial scale is quality control. Established imaging techniques like lock‐in thermography or luminescence imaging are frequently used for this purpose. While these techniques allow for the lateral detection of defects, they cannot provide information on the vertical position of the defect in the OPV stack. Here, we present an approach to overcome this limitation. A femtosecond‐laser is deployed to introduce well‐defined artificial calibration defects selectively into both the interface and the bulk active layer of inverted P3HT:PCBM bulk heterojunction cells during device fabrication. The defective cells are then characterized using J‐V analysis and several nondestructive imaging methods (dark lock‐in thermography, photoluminescence, and electroluminescence imaging). The distinct response for each defect in the different imaging methods enables us to uniquely distinguish between bulk and interface defects. This allows to study surface recombination under most controlled conditions.
Keywords: imaging; organic solar cells; dark lock-in thermography; electroluminescence; photoluminescence; quality control

Flexible Solar Cells - Maisch, Philipp; Lucera, Luca; Egelhaaf, Hans-Joachim; Brabec, Christoph (Flexible Carbon-based Electronics, 2018)
This third volume in the Advanced Nanocarbon Materials series covers the topic of flexible electronics both from a materials and an applications perspective. Comprehensive in its scope, the monograph examines organic, inorganic and composite materials with a section devoted to carbon-based materials with a special focus on the generation and properties of 2D materials. It also presents carbon modifications and derivatives, such as carbon nanotubes, graphene oxide and diamonds. In terms of the topical applications covered these include, but are not limited to, flexible displays, organic electronics, transistors, integrated circuits, semiconductors and solar cells. These offer perspectives for today?s energy and healthcare challenges, such as electrochemical energy storage and wearable devices. Finally, a section on fundamental properties and characterization approaches of flexible electronics rounds off the book. Each contribution points out the importance of the structure-function relationship for the target-oriented fabrication of electronic devices, enabling the design of complex component

Fully Printed Infrared Photodetectors from PbS Nanocrystals with Perovskite Ligands - Yousefiamin, Amirabbas; Killilea, Niall Andrew; Sytnyk, Mykhailo; Maisch, Philipp; Tam, Kwok-Kan; Egelhaaf, Hans-Joachim; Langner, Stefan; Stubhan, Tobias; Brabec, Christoph; Rejek, Tobias; Halik, Marcus; Poulsen, Katharina; et al. (ACS nano, 2019)
Colloidal nanocrystals from PbS are successfully applied in highly sensitive infrared photodetectors with various device architectures. Here, we demonstrate all-printed devices with high detectivity (similar to 10(12) cm Hz(1/2) /W) and a cut-off frequency of >3 kHz. The low material consumption (<0.3 mg per detector) and short processing time (14 s per detector) enabled by the automated printing promises extremely low device costs. To enable all-printed devices, an ink formulation was developed based on nanocrystals stabilized by perovskite-like methylammonium iodobismuthate ligands, which are dispersed in a ternary solvent. Fully inkjet printed devices based on this solvent were achieved with printed silver electrodes and a ZnO interlayer. Considerable improvements were obtained by the addition of small amounts of the polymer poly(vinylpyrrolidone) to the ink. The polymer improved the colloidal stability of the ink and its film-formation properties and thus enabled the scalable printing of single detectors and detector arrays. While photoconductors were shown here, the developed ink will certainly find application in a series of further electronic devices based on nanocrystals from a broad range of materials.
Keywords: colloidal nanocrystals; infrared detectors; inkjet printing; PbS; solution processing

Fully printed organic solar modules with bottom and top silver nanowire electrodes - Tam, Kai Cheong; Kubis, Peter; Maisch, Philipp; Brabec, Christoph; Egelhaaf, Hans-Joachim (Progress in Photovoltaics, 2021)
One of the advantages of organic photovoltaics (OPV) over other contemporary technologies is its relative ease of processing. There are, however, very few works that have realized fully printed devices, including the bottom electrode, let alone with a scalable process in a reasonable device size (>1 cm(2)). In this work, design steps and optimization processes towards fully printed OPV modules with scalable processes are demonstrated for the first time. An overview on issues related to upscaling with printed electrodes is first provided. The various issues are then addressed by a rational design process supported by measurements and calculations. Finally, a set of fully printed OPV modules are fabricated using these optimized parameters that have over 3.5-cm(2) active area with 5% efficiency. For the first time, this work has also demonstrated the process compatibility of fully printed device structures with non-fullerene acceptor systems, which enables more design opportunities for the current generation of high-performance OPV materials.
CRIS-Team WoS Importer:2021-12-31